Konsep Poligami Perspektif Rasyid Ridha dan Muhammad Syahrur - Martai Martai (UNIVERSITAS BONDOWOSO, 2023)
The phenomenon of polygamy continues to grow, opposing groups (feminists) strongly oppose the practice of polygamy. They state that polygamy is haram because of the impossibility of men doing justice to their wives. On the other hand, those who are pro-polygamy, based on their understanding of religious texts, argue that polygamy is not only lawful but also a virtue.Were it not for his virtue, it would not be possible for the Messenger of Allah to do it for up to nine wives. Efforts to inform the classical interpretations do not seem to be able to stop this polemic as long as the conflict of interest still plagues each group.To resolve this polemic is to reinterpret polygamy texts according to the current context.This sis intended so that the results of understanding the text are not only subjective, but more objective so that the law can be felt as a whole.Departing from the phenomenon, this study tries to re-examine the concept of polygamy.Muhammad Syahrur's polygamy concept in the book al-Kitab and al-Qur'an Qira'ah Mu'ashirah and Nahwa Usul Jadidah li al-Fiqh al-Islamiy (Fiqh al-Mar'ah) and Rashid Rida in Tafsir al-Qur'an al-Hakim, who is famous for his Tafsir al-Manar, may be able to answer the tensions between pro and anti-polygamy groups.These two innovative modern figures discuss the details of the concept of polygamy contextually.In this study, the concepts of these two figures were analyzed by content analysis.Then we get the two concrete concepts, the implications, and the relevance of the two concepts to the demands of the times.In the end, after being parsed and analyzed, the concept of Rasyid Rida puts forward the socio-historical aspect in dealing with polygamy.From that, he concluded that polygamy is permissible in an emergency.The husband must ensure justice for his wives.If he is still worried that there will be injustice to his wives, then polygamy is forbidden for him.Meanwhile, Muhammad Syahrur with his linguistic logic (al-nazhariyyah al-hudÃ»diyyah) only limited the permissibility of polygamy to the mothers of orphans, the orphans were under his care.Polygamy is freely prohibited in virgin women.